PIMPINELLA PRUATJAN MOLK. AS A POTENTIAL ANTI-DIABETIC NEUROPATHY WITH ANTIOXIDANT MECHANISMS: A REVIEW - Dewi, Trisni Untari; Mondiani, Yeni Quinta; Rukmi, Kartika Widya; Munawaroh, Fauziyatul; Rusmajati, Jetty; Batubara, Irmanida (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Medicinal plant utilization in the clinical management of metabolic disorders, including Diabetes Mellitus (DM) and its associated complications, has gained considerable scientific attention in recent decades. Their perceived tolerability positions them as viable complementary or adjunct options to standard pharmacological regimens. Purwoceng (Pimpinella pruatjan Molk.) is a plant indigenous to Indonesia that demonstrates notably high concentrations of antioxidant constituents. Given that oxidative stress constitutes a fundamental driver in the pathophysiology of DM, it is implicated in the development of complications including diabetic peripheral neuropathy. Objective: To review existing evidence on the potential of purwoceng in reducing blood glucose levels and repairing nerve damage in diabetic neuropathy, including its mechanisms, active compounds, and toxicity profile. Methods: A literature review was conducted using keywords including Pimpinella pruatjan/Molk, Purwoceng, Antioxidant, Diabetes Mellitus, Diabetic Neuropathy, and secondary metabolites. Relevant studies were selected and critically reviewed. Results: Several studies identified secondary metabolites in purwoceng, including phenolics, flavonoids, tannins, coumarins, saponins, terpenes, and steroids. These compounds exhibit antioxidant and anti-inflammatory properties, suggesting potential benefits in reducing hyperglycemia and preventing or repairing nerve damage in diabetic neuropathy. Available evidence also indicates no significant acute toxicity in renal and hepatic organs. Conclusion: Purwoceng exhibits promising potential as an adjunctive therapeutic agent in the management of Diabetes Mellitus and its neuropathic complication, mediated principally through antioxidant and anti-inflammatory mechanisms, with a favorable preliminary safety profile. Rigorous clinical investigations are warranted to substantiate its efficacy and safety in human subjects.